Estudo sistemático das propriedades estruturais e magnéticas de amostras policristalinas do sistema PrxY1-xBa2Cu3O7-d - Romano, Cecilia Stari (Universidade Federal de São Carlos, 2008)
One of the most studied high TC superconductor is the YBa2Cu3O7 (Y-123) as well as the different substitutions on the Y site for different rare earth elements. Generally, this does not show important effects on the magnetic and superconducting properties. One exception to this behavior is the partial or total substitution of Y for Pr (PrxY1-xBa2Cu3O7 PrY-123) for which critical temperature diminishes and superconductivity is quenched for a certain value of x. However, the mechanism responsible for this suppression is not understood yet existing in the literature a great controversy about it. Moreover, in the last decade, superconductivity in Pr-123 samples has been reported for some authors where the method of syntheses appears to be responsible for the formation, or not, of the superconducting phase. These results opening still more the discussion of this topic. While for some authors o Pr-123 is an intrinsic non superconductor, for others is the method of syntheses that influences significantly in the formation of the probable superconducting phase. In this thesis we present a systematic study on the influence of synthesis conditions in the superconducting properties of polycrystalline samples of PrY-123. For this study, bulk polycrystalline samples were prepared by following a chemical route based in a modified polymeric precursor method. This method is recognized to produce very homogeneous samples reducing the presence of secondary phases, in comparison with the traditional method of solidstate reaction. Also, an essential part of this work was study how internal atmosphere using during both calcination and sinterization is influencing on the final properties of the samples. For study this we used oxygen and argon atmosphere. The phase purity and the structural characteristics of our samples were confirmed by scanning electron microscopy (SEM), x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS). We have measured the temperature dependence of both DC and AC magnetic susceptibility for the study of the superconductor properties and I ×V curves. The results indicated that for samples synthesized on argon atmosphere, the whole YPr- 123 family, including pure Pr-123, is superconductor in temperatures between of about 90 K. We also found that the superconducting transition temperature increase in samples prepared in argon respect to the samples prepared in oxygen (for the same Pr composition), when Pr concentration is less than 0.5. At the end of this work, through the results attained on the master work of Leonélio Cichetto Júnior (belonging to the same research group), we verified that YPr-123 singlecrystalline samples obeyed the same Physics that we describe for polycrystalline samples. Therefore, we can affirm that the existence of superconductivity for all the family YPr-123 is intrinsically associated to, and only to, syntheses conditions (calcination and sinterization). Both results (for polycrystalline and for single-crystals samples) demonstrate that theories for explain the Pr-123 non superconducting must be revised.
Keywords: Física da matéria condensada; Supercondutividade; Cerâmica - síntese; CIENCIAS EXATAS E DA TERRA::FISICA